PENGARUH RETURN ON ASSET (ROA) DAN DEBT TO ASSET RATIO (DAR) TERHADAP HARGA SAHAM (Pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2016-2023) - Putri, Tiara Amelia; Sawukir (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether there is an effect of Return On Asset (ROA) and Debt to Asset Ratio (DAR) on Stock Prices in Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange for the Period 2016 - 2023. The method in this research is quantitative type with descriptive method. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics to test partial regression coefficients and using f-statistics to calculate objections together (simultaneously) with a significant level of 5%. In addition, a classical assumption test is also carried out which includes normality test, multicorelity test, heteroscedasticity test and autocorrelation test. The results showed that Return On Asset (ROA) produced a significance value of 0.3849> 0.05 and tcount 0.876079 < t table 2.00575. it can be concluded that Return On Asset (ROA) has no effect on stock prices. While the Debt to Asset Ratio (DAR) produces a significance value of 0.0002 <0.05 and tcount -4.045130> t table 2.00575, it can be concluded that the Debt to Asset Ratio (DAR) has an effect on stock prices. Then Return On Asset (ROA) and Debt to Asset Ratio (DAR) simultaneously obtained a value (f-statistic) of 0.000577 <0.05 and fcount 8.612737> ftabel 2.171626. it can be concluded that in a simultaneous variable that Return On Asset (ROA) and Debt to Asset Ratio (DAR) have a significant effect on stock prices.